Variability of annual rainfall in São Paulo Metropolitan Region (RMSP) and Cantareira System: classification and frequency of the standard-years - Fontão, Pedro Augusto Breda [UNESP]; Zavattini, João Afonso [UNESP] (Revista Brasileira de Geografia Fisica, 2019)
This study aims to establish standard-years and extreme-years of rainfall (wet and dry) through a research evaluating the variability of the annual precipitations in the Metropolitan Region of São Paulo (MRSP), the largest urban cluster in the southern hemisphere of the planet, and in the Cantareira System, main system of urban water supply of the metropolis of São Paulo. Identifying 'standard-years', especially extreme periods, contributes to discern periods of irregularities in the atmospheric circulation, making it possible to proceed with a more detailed analysis of the rainfall rhythm. Therefore, rainfall data from the historical serie from 1985 to 2014 were used. After collecting, organizing and mapping the data, the method of Sturge's formula was applied to assign the ranges of data representing the volume of rainfall and the method of geostatistical interpolation of ordinary kriging was applied to map the data. From the results obtained, analyzes were carried out on the temporal and spatial variability of the precipitations, making it possible, for both regions, to classify each of the 30 years of the period as: dry, tending to dry, habitual, tending to rainy or rainy. It stands out the existence of some years with the dissimilar pattern between the MRSP and the Cantareira System, resulting in possible impacts on human activities.
Variabilidade das chuvas anuais na Região Metropolitana de São Paulo (RMSP) e no Sistema Cantareira: classificação e frequência dos anos-padrão
Keywords: Climate variability; Climatology; Precipitation; Sturge's formula; Water supply